Factors Influencing Decisions to Visit Private Parks: The Case of Araluen Botanic Park WA - Lee, Sean; Phau, Ian; Quintal, Vanessa (Australian and New Zealand Marketing Academy, 2012)
This paper closes an inherent gap in the literature on research on private parks. Specifically, the aim of the study is threefold: (a) identify the push and pull factors that influence decisions to visit private parks; (b) examine differences in these push and pull factors for different socio-demographic groups; and (c) investigate the interrelationships among these push and pull factors. Data were collected from 228 visitors intercepted at various locations at a private park. The survey instrument assessed the reasons for push and pull factors. The results of a factor analysis revealed three push factors and three pull factors. A general correlation analysis on the interrelationship among push and pull factors was also conducted. This study provides useful managerial and practical implications for park managers, policy makers and communications strategists to gain an understanding of how push and pull factors affect tourists and their destination choice of private parks.